(untitled) (Aptisi Transactions on Technopreneurship (ATT), 2023)
The digital era has opened opportunities for entrepreneurs (technopreneurs) to enhance their performance and market reach. However, a deep understanding of how the use of digital platforms, digital customer engagement, and operational efficiency through digitalization contribute to entrepreneurial success is still limited. This study aims to analyze the impact of digital platform usage, digital customer engagement, and operational efficiency through digitalization in the context of entrepreneurial success. The primary goal is to identify and measure the extent to which these three variables contribute to entrepreneurial success in the digital era. This research employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS software. This approach was chosen due to its capability in handling complex models and exploratory data. Data was collected from an online survey completed by entrepreneurs actively using digital platforms in their businesses. The sample consists of 300 respondents representing various industry sectors and business sizes. The study’s findings indicate that the use of digital platforms significantly enhances customer engagement and operational efficiency. Digital customer engagement plays a vital role in building loyalty and trust, which further influences business success. Operational efficiency through digitalization also contributes significantly to increasing productivity and reducing operational costs. Overall, this research provides empirical evidence that effective integration of digital technologies is key to entrepreneurial success in the digital era.